Urban Agriculture: A Solution to Nature - Shishira Kanta Behera, Ajay Kumar Pattnayak, Kishor Chandra Senapati (International Journal of Modern Agriculture, 2020)
Urbanization and feasible agricultural practice are major cultural difficulties. By lessening nourishment miles and associating individuals with nature, nourishment development in urban communities has a few significant focal points. Nonetheless, because of further urban improvement “(peri-) urban farming (UPA)" is under risk. To reinforce UPA, we contend for considering UPA as a "nature-based arrangement (NbS)" supporting fundamental methodologies for cultural difficulties. Notwithstanding, scholastic information on UPA's commitment to different cultural difficulties of urbanization is as yet divided. This investigation addresses the hole by leading a fundamental writing audit, joining 166 scholarly articles concentrating on the worldwide north. The consequences of the audit show that UPA adds to ten key cultural difficulties of urbanization: environmental change, nourishment security, biodiversity and biological system administrations, farming heightening, asset proficiency, urban recharging and recovery, land the board, general wellbeing, social union, and financial development. The importance of UPAlies in its multifunctionality in giving social, monetary and natural co-advantages and biological system administrations. While executing UPA, social, institutional, monetary, specialized, geological, and environmental drivers and imperatives should be considered. To upscale UPA effectively, the examination builds up an integrative evaluation system for assessing the usage and effectiveness of UPA. This structure ought to be tried in light of the case of palatable urban areas.